Gigantic intracranial hydatid cyst and MRI findings with a case report - Koç, Mustafa; Altinsoy, Hasan Baki (My University, 2007)
Hydatid cyst is a parasitic infestation with rare presentation in the cerebrum. Hydatid cyst disease is rare in the cerebrum and lebions are usaally single, accounting for only 1,6-5,2 % of all hydatid cysts. The differential diagnosis of cerebral cystic echinococcosis includes abscess, cystic tumor, arachnoid cyst, and porencephalic cyst. In this report, we aim to present MRI findings of a gigantic intracranial hydatid cyst mass which ihas not been previously described in this size before.
Dev serebral kist hidatik: MRG bulgulari ile olgu sunumu
Keywords: Brain; Echinococcosis; Magnetic resonance imaging